PEMBENTUKAN KONSEP DIRI SATUAN PASPAMPRES RI - Melani Kurniasih Sormin; Ilham Prisgunanto (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The results showed that individual PASPAMPRES personnel have thoughts and self-assessment of quality and are superior, have a favorable opportunity for promotion compared to other unit personnel. This study aims to determine how the formation of self-concept in the personnel of the PASPAMPRES unit based on the situation and facts where PASPAMPRES is an elite unit containing selected and qualified soldiers who have certain skills and privileges to be able to carry out Presidential VVIP security duties. A strict personnel admission selection where not all TNI soldiers can pass and have the desired qualifications make PASPAMPRES personnel called superior and elected personnel. The reason this research was conducted was to find out how this situation had its own impact on the self-concept of the selected PASPAMPRES personnel. The theory used is the Symbolic Interactionism theory by George Herbert Mead, Self-Concept and Group Thought Theory. This research methodology uses a constructivism paradigm with a qualitative approach and data collection techniques using interviews. The focus of this research focuses on how the mind, self, and society as well as the climate of the PASPAMPRES unit can influence the formation of personnel self-concept.